APLIKASI PENGOLAHAN DATA INVENTARIS PERALATAN PRAKTEK PADA SMK PRASASTI KARANG BERAHI KOTA JAMBI - Budiarti, Rike Limia; Sany, Ezrifal; Wahid, Nur (FORTECH (Journal of Information Technology), 2017)
From background found in SMK Prasasti Karang Berahi Kota Jambi in the application of inventory data processing is still relatively simple, inventory data inventory practice equipment done manually by writing / note on the agenda book and some enter data is done by using microsoft office application. To help these activities need to be created or designed a program or application that can be used together and able to run on all computers that are installed software browsing. Application Data Processing Inventory Equipment Practice is built using a web-based technology with PHP scripting language, MySQL database, and Freamwork. With the implementation of the Inventory Data Processing Applications that are web based in this SMK Prasasti Karang Berahi so that it affects the school, and so forth and helps administrative data collection staff in delivering the inventory of practice equipment ofline and online because the data presented quickly